FeRu / CeO2 catalyst as well as preparation method and application thereof

By loading Fe and Ru on CeO2 nanosphere support, FeRu/CeO2 catalyst was prepared, which solved the problems of high cost and low reaction efficiency of existing hydrogenolysis catalysts, and achieved efficient and low-cost plastic hydrogenolysis, with liquid product selectivity up to 86.4%.

CN119771445APending Publication Date: 2025-04-08CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510200765.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing hydrogenolysis catalysts have problems such as high cost, low reaction efficiency and excessive generation of by-product methane during the plastic hydrogenolysis process.

Method used

The FeRu/CeO2 catalyst was used, which was formed by supporting metal Fe and Ru on CeO2 nanosphere support, with the content of precious metal Ru only 1.6%, and the synthesis process was simplified by a one-step impregnation method.

Benefits of technology

It achieves efficient hydrolysis of plastics under mild conditions, with a complete conversion time of only 1 hour, and the liquid product selectivity reaches 86.4%, significantly reducing catalyst cost and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771445A_ABST
    Figure CN119771445A_ABST
Patent Text Reader

Abstract

The invention discloses a FeRu / CeO2 catalyst as well as a preparation method and application thereof, relates to the technical field of catalysts, and solves the problems of high cost, low reaction efficiency and the like of an existing hydrogenolysis catalyst. The catalyst is formed by loading metals Fe and Ru on a CeO2 nanosphere carrier, and the loading capacities are respectively 0.2-1.0 wt% and 1.0-2.0 wt%. The preparation method comprises the following steps: dissolving cerous nitrate and PVP (Polyvinyl Pyrrolidone) in ethylene glycol, stirring, dropwise adding deionized water, transferring a clarified liquid into a polytetrafluoroethylene kettle for hydrothermal reaction, completely cooling, centrifugally washing, and drying overnight to obtain CeO2 nanospheres; the preparation method comprises the following steps: pretreating CeO2 nanospheres in hydrogen-argon mixed gas, dispersing in deionized water, respectively adding aqueous solutions of RuCl3. 3H2O and FeCl3. 6H2O, stirring at room temperature, transferring into an oil bath until all water is evaporated, and carrying out hydrogen-argon mixed gas reduction treatment on a product to obtain the catalyst. The catalyst can be used for catalyzing the hydrogenolysis reaction of the plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a FeRu / CeO2 catalyst and a preparation method and application thereof. Background Art

[0002] Plastic products are everywhere in modern life. The global annual output of plastics is growing rapidly. It is expected that by 2050, the annual output will climb to 687 million tons. However, the recycling of waste plastics is not optimistic. Only less than 10% of waste plastics can be recycled. This not only causes a huge waste of resources, but also causes serious environmental pollution and threatens the life safety of animals and plants.

[0003] In this context, chemical recycling strategies have emerged. They can convert waste plastics into high-value-added products such as fuels and lubricants, which is in line with the concept of circular economy and is regarded as a very promising recycling strategy. Among them, hydrogenolysis technology has attracted much attention due to its mild reaction conditions, narrow distribution of hydrocarbon products and low environmental impact. Commonly used hydrogenolysis catalysts are Pt-based and Ru-based catalysts. Ru-based catalysts show higher hydrogenolysis activity than Pt due to their unique CC bond cleavage ability. However, the higher reactivity of Ru metal can easily trigger cascade hydrogenation reactions, resulting in excessive production of by-product methane. This problem needs to be solved urgently.

[0004] In order to optimize the reaction process of Ru-based catalysts, researchers have made many attempts. For example, by optimizing the metal-support interaction (Nat. Commun. 2022, 13, 5186), constructing sub-nanometer or even single-atom scale sites (ACS Catal. 2022, 12, 4618-4627), highly selective liquid products are generated. However, these strategies are often accompanied by sacrificing the reactivity of active metals and even introducing stability issues. Other studies have found that the incorporation of a second metal can flexibly regulate the charge density and local structure around the active site, thereby effectively regulating the performance of plastic hydrogenolysis. In the latest literature study, the introduction of a second metal Pt to dilute Ru successfully increased the yield of liquid hydrocarbons to 81.2%. However, the amount of precious metal Pt used in this method is as high as 20wt%, which significantly increases the catalyst cost (Nat. Commun. 2024, 15, 10573). Therefore, the development of an economical and effective method to regulate Ru-based catalysts for plastic hydrogenolysis has important application value.

[0005] In fact, in past research and practice, technicians in this field have tried to solve the above problems through different approaches, and some of the results are presented in the form of patents, but they also have some shortcomings. For example, patent CN202311561046.6 provides a method for preparing a sodium titanate nanowire-loaded ruthenium catalyst. Although the catalyst can show high selectivity for liquid hydrocarbon products under relatively mild conditions, the synthesis steps of the catalyst are relatively complicated, and the hydrogenolysis reaction time is long, resulting in high time costs. Patent CN202411287503.1 discloses a new bimetallic alloy RuxNiy / SiO catalyst for hydrogenolysis of polyethylene plastics into liquid fuel. The complete conversion of polyethylene can be achieved by reacting at 250°C and 1-4MPa H2 for 12 hours, and C5~C 40 The yield can reach up to 96.8%. However, the catalyst has the problems of high Ru content and high hydrogen pressure, which increases the catalyst cost. Moreover, as the Ni content increases, the liquid selectivity increases, but the time for complete conversion gradually increases to 36h, the reaction efficiency is low, and the energy consumption is greatly increased. Summary of the invention

[0006] In order to solve the problems of high cost and low reaction efficiency of existing hydrogenolysis catalysts, the present invention proposes a novel bimetallic FeRu / CeO2 catalyst for hydrogenolysis of polyethylene into liquid hydrocarbons with high efficiency, high selectivity and low cost and a synthesis method thereof.

[0007] The technical solution of the present invention is as follows:

[0008] The present invention provides a FeRu / CeO2 catalyst, wherein the FeRu / CeO2 catalyst is formed by co-loading metal Fe and Ru on a CeO2 nanosphere carrier;

[0009] The loading amounts of Fe and Ru are 0.2-1.0 wt% and 1.0-2.0 wt% respectively.

[0010] The present invention also provides a method for preparing a FeRu / CeO2 catalyst, comprising the following steps:

[0011] S1. Dissolve cerium nitrate and PVP in ethylene glycol, stir and add deionized water dropwise, transfer the liquid to a polytetrafluoroethylene kettle for hydrothermal reaction after the liquid is clarified, and after the reaction is completed, cool completely, wash with deionized water for multiple centrifugation and dry overnight to obtain CeO2 nanospheres;

[0012] S2. Pretreat CeO2 nanospheres in a hydrogen-argon mixed gas, then disperse them in deionized water, add aqueous solutions of RuCl3·3H2O and FeCl3·6H2O respectively, stir at room temperature and transfer to an oil bath until all the water evaporates, and collect the products and reduce them with a hydrogen-argon mixed gas to obtain a FeRu / CeO2 catalyst.

[0013] Preferably, the usage ratio of cerium nitrate, PVP, ethylene glycol and deionized water in step S1 is 2.0 g: 0.8 g: 60 mL: 4 mL.

[0014] Preferably, the temperature of the hydrothermal reaction in step S1 is 140-170° C., and the reaction time is 8-24 h.

[0015] Preferably, the hydrogen content in the hydrogen-argon mixed gas in step S1 and step S2 is 5%.

[0016] Preferably, the pretreatment temperature in step S2 is 200-300° C., and the pretreatment time is 1-2 h.

[0017] Preferably, in step S2, the stirring time is 30 min, and the oil bath temperature is 80°C.

[0018] Preferably, the temperature of the reduction treatment in step S2 is 200-300° C., and the reduction treatment time is 1-2 hours.

[0019] The present invention also provides an application of the FeRu / CeO2 catalyst or the FeRu / CeO2 catalyst prepared by the above preparation method, which is specifically used for catalyzing the hydrogenolysis reaction of plastics.

[0020] Preferably, the hydrogenolysis reaction specifically comprises the following steps:

[0021] The FeRu / CeO2 catalyst and low-density polyethylene physically mixed in a mass ratio of 1:10 were added to the reactor. After the reactor was sealed, 0.1MPa N2 was filled as an internal standard and 1-3MPa H2 was filled as a reaction gas. The reaction was carried out at 200-300°C for 0.5-1h.

[0022] Compared with the prior art, the specific beneficial effects of the present invention are:

[0023] 1. The material synthesis method proposed in the present invention has remarkable simplicity and innovation, and the FeRu / CeO catalyst can be successfully synthesized by a one-step impregnation method. The content of the noble metal Ru is only 1.6%, which greatly reduces the cost of the catalyst compared with the high content of noble metals commonly used in the prior art, thus giving the present invention an outstanding cost advantage.

[0024] 2. The present invention focuses on the field of plastic hydrogenolysis reaction and exhibits excellent performance. The reaction can be carried out under mild and efficient conditions, with a reaction temperature of only 250°C, a hydrogen pressure of 1-3 MPa, and a complete conversion time of the plastic of only 1 hour. This efficient reaction process not only greatly improves the reaction efficiency, but also significantly reduces the energy consumption during the reaction process, fully demonstrating the advantages of the present invention in energy utilization.

[0025] 3. The catalyst prepared by the present invention performs excellently in improving the selectivity of liquid products. The introduction of Fe effectively changes the local environment of Ru, optimizes the adsorption and desorption process of alkane intermediates and active hydrogen, and thus effectively inhibits the occurrence of cascade hydrogenation reactions. The selectivity of liquid products can reach up to 86.4%. This achievement greatly improves the value of the product and provides strong technical support for the industrial application of plastic hydrogenolysis reactions.

[0026] In summary, the catalyst prepared by the present invention not only has a simple synthesis method and low cost, but also exhibits outstanding advantages of high activity, high selectivity, low energy consumption and high product value when applied to plastic hydrogenolysis reactions, providing a highly potential solution for the field of polyethylene plastic hydrogenolysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM image of the FeRu / CeO2 catalyst prepared in Example 1;

[0028] Figure 2 HRTEM image and EDX image of the FeRu / CeO2 catalyst prepared in Example 1;

[0029] Figure 3 The XRD pattern of the FeRu / CeO2 catalyst prepared in Example 1;

[0030] Figure 4 is the carbon number distribution diagram of the product after hydrogenolysis of low density polyethylene in Example 1;

[0031] Figure 5 Schematic diagram of the test results of the effect of reaction time on conversion rate and yield in Example 2;

[0032] Figure 6 Schematic diagram of the test results of the effect of reaction temperature on conversion rate and yield in Example 3;

[0033] Figure 7 Schematic diagram of the test results of the effect of hydrogen pressure on conversion rate and yield in Example 4;

[0034] Figure 8 Schematic diagram of the test results of the effect of the amount of FeCl3 solution added on the conversion rate and yield in Example 5. DETAILED DESCRIPTION

[0035] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0036] Example 1.

[0037] In this embodiment, the catalyst uses CeO2 nanospheres as a carrier, RuCl3·3H2O and FeCl3·6H2O as metal salt precursors, and the Ru loading in the catalyst is 2wt%, and the Fe loading is 0.5wt%.

[0038] The specific steps of preparing the above catalyst are as follows:

[0039] (1) Weigh 2.0 g of cerium nitrate and 0.8 g of PVP and dissolve them in 60 mL of ethylene glycol. Stir vigorously, slowly add 4 mL of deionized water, stir at room temperature for 30 min, transfer to a 100 mL polytetrafluoroethylene kettle and perform hydrothermal treatment at 160 ° C for 8 h. After the reaction is completed, wait for complete cooling, wash with deionized water several times by centrifugation and dry overnight to obtain CeO2 nanospheres.

[0040] (2) Weigh 261.5 mg of RuCl3·3H2O and dissolve it in 10 mL of deionized water to obtain a 0.1 M RuCl3 solution. Weigh 60.0 mg of FeCl3·6H2O and dissolve it in 15 mL of ethanol to obtain a 0.015 M FeCl3 solution.

[0041] (3) Weigh 240.0 mg of pretreated CeO2 nanospheres (pretreatment conditions: 250°C, 2 h) and disperse them in 30 mL of deionized water. Then, add 0.476 mL of RuCl3 solution and 1.45 mL of FeCl3 solution in step (1) respectively. After stirring for 30 min, evaporate the water in an 80°C oil bath.

[0042] (4) Collect the product obtained in step (2), grind it thoroughly, raise the temperature to 250° C. at a rate of 5° C. / min in a 5% H 2 / Ar mixed gas, and maintain it for 2 h to obtain a FeRu / CeO 2 catalyst.

[0043] (5) Add 100 mg of FeRu / CeO2 catalyst and 1000 mg of low-density polyethylene into the reactor, mix well, flush with N2 10 times, then fill with 0.1 MPa N2 and 2 MPa H2, and heat to 250°C for reaction for 1 h.

[0044] (6) After the reaction is completed, the reactor is cooled to below 10° C., the top gas product is collected, and qualitative and quantitative analysis is performed by gas chromatography; a dichloromethane solution containing 10 mg of mesitylene as an internal standard is prepared, and the liquid product is dissolved and collected, and qualitative and quantitative analysis is performed by gas chromatography-mass spectrometry; the residual solid in the reactor is collected, dried overnight, and weighed.

[0045] The results showed that under the catalysis of FeRu / CeO2, low-density polyethylene was completely converted and the liquid yield was as high as 86.4%.

[0046] The SEM image of the FeRu / CeO2 catalyst prepared in this example is shown in FIG. Figure 1 As shown, it can be seen that the catalyst has a regular nano-spherical structure. The uniform spherical structure provides a relatively regular loading base for metal Fe and Ru, which is conducive to achieving a more uniform loading distribution.

[0047] Figure 2 The results show that the crystal plane of CeO was observed, proving the existence of CeO carrier and the integrity of its crystal structure. EDX image information shows that Ru and Fe were successfully incorporated and evenly distributed on the surface of CeO2. The Overlap diagram can intuitively show that the distribution of Ru and Fe elements has a high degree of overlap, indicating that the introduction of Fe changes the local environment of Ru. Ru and Fe may have a synergistic effect in the catalyst, making the catalyst show high liquid selectivity in the plastic hydrogenolysis reaction.

[0048] Figure 3 This is the XRD pattern of the FeRu / CeO2 catalyst, showing the diffraction peaks of standard CeO2 crystals.

[0049] Figure 4 The carbon number distribution diagram of the product after hydrogenolysis of low-density polyethylene in this embodiment shows that the liquid product is C 20 Centrally distributed.

[0050] Example 2.

[0051] In this example, the same FeRu / CeO2 catalyst as in Example 1 was used. Similarly, at 250°C and 2MPa H2, the hydrogenolysis reaction time was changed to mainly explore the effect of different reaction times. The test results are shown in Figure 2. Figure 5 As shown, at the hydrogenolysis reaction times of 0.5 h, 0.75 h and 1 h, the conversion rates were 18.3%, 95.2% and 100% respectively, and the liquid oil yields were 10.0%, 80.4% and 86.4% respectively.

[0052] Example 3.

[0053] In this example, the same FeRu / CeO2 catalyst as in Example 1 was used. Similarly, the reaction was carried out under 2MPa H2 for 1 h, and the hydrogenolysis reaction temperature was changed to mainly explore the effect of the reaction temperature. Figure 6 It was shown that the conversion rates at hydrogenolysis temperatures of 240°C, 250°C and 260°C were 55.7%, 100% and 100% respectively, and the liquid oil yields were 43.4%, 86.4% and 65.6% respectively.

[0054] Example 4.

[0055] In this example, the same FeRu / CeO2 catalyst as in Example 1 was used, and the reaction was carried out at 250°C for 1 h. The hydrogen pressure was changed to mainly explore the effect of hydrogen pressure on the reaction results. Figure 7 It is shown that the conversion rates at 1MPa, 2MPa and 3MPa hydrogen pressures are 75.8%, 100% and 100% respectively, and the liquid oil yields are 50.5%, 86.4% and 88.8% respectively.

[0056] Example 5.

[0057] In this example, the amount of FeCl3 solution added in Example 1 was changed to 0.58 mL, 1.45 mL, and 2.9 mL, respectively. Similarly, the reaction was carried out at 250°C and 2 MPa H2 for 1 h, mainly to explore the effect of Fe loading on the reaction. Figure 8 It is shown that at Fe loadings of 0.2wt%, 0.5wt%, and 1.0wt%, the conversion rates are 100%, 100%, and 52%, respectively, and the liquid oil yields are 63.4%, 86.4%, and 45.2%, respectively.

[0058] The above test results show that when the reaction time reaches 1h, the complete conversion of plastics can be basically achieved, and the liquid oil yield is high, and 250℃ is the optimal reaction temperature. Appropriately increasing the hydrogen pressure is helpful to improve the conversion rate and liquid oil yield, and the cost performance is higher at 2MPa. Under the conditions of 250℃ and 2MPa H for 1h, when the Fe loading amount is from 0.2wt% to 0.5wt%, the conversion rate is 100%, and the liquid oil yield increases from 63.4% to 86.4%; when the loading amount increases to 1.0wt%, the conversion rate drops to 52%, and the liquid oil yield drops to 45.2%, indicating that the appropriate amount of Fe loading is preferably 0.5wt%, which helps to improve the conversion rate and liquid oil yield.

[0059] In summary, the FeRu / CeO2 catalyst synthesized by the one-step impregnation method of the present invention has a low content of precious metal Ru. Compared with the high content of precious metals in the prior art, the catalyst cost is low and has significant cost advantages. Applied to the hydrogenolysis reaction of plastics, the reaction conditions are mild and efficient, and the complete conversion time only takes 1 hour, which greatly improves the reaction efficiency and reduces the energy consumption during the reaction. In addition, the introduction of Fe changes the local environment of Ru, optimizes the adsorption and desorption of alkane intermediates and active hydrogen, inhibits cascade hydrogenation, and ultimately significantly improves the selectivity of liquid products and improves the product value. The liquid selectivity is as high as 86.4%.

[0060] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A FeRu / CeO2 catalyst, characterized in that: The FeRu / CeO2 catalyst is formed by co-loading metal Fe and Ru on a CeO2 nanosphere carrier; The loading amounts of Fe and Ru are 0.2-1.0 wt% and 1.0-2.0 wt% respectively.

2. A method for preparing a FeRu / CeO2 catalyst, characterized in that: The following steps are included: S1. Dissolve cerium nitrate and PVP in ethylene glycol, stir and add deionized water dropwise, transfer the liquid to a polytetrafluoroethylene kettle for hydrothermal reaction after the liquid is clarified, and after the reaction is completed, cool completely, wash with deionized water for multiple centrifugation and dry overnight to obtain CeO2 nanospheres; S2. Pretreat CeO2 nanospheres in a hydrogen-argon mixed gas, then disperse them in deionized water, add aqueous solutions of RuCl3·3H2O and FeCl3·6H2O respectively, stir at room temperature and transfer to an oil bath until all the water evaporates, and collect the products and reduce them with a hydrogen-argon mixed gas to obtain a FeRu / CeO2 catalyst.

3. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The usage ratio of cerium nitrate, PVP, ethylene glycol and deionized water in step S1 is 2.0 g: 0.8 g: 60 mL: 4 mL.

4. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step S1 is 140-170° C., and the reaction time is 8-24 hours.

5. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The hydrogen content in the hydrogen-argon mixed gas in step S1 and step S2 is 5%.

6. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The pretreatment temperature in step S2 is 200-300° C., and the pretreatment time is 1-2 hours.

7. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The stirring time in step S2 is 30 min, and the oil bath temperature is 80°C.

8. The method for preparing the FeRu / CeO2 catalyst according to claim 2, characterized in that: The temperature of the reduction treatment in step S2 is 200-300° C., and the reduction treatment time is 1-2 hours.

9. A use of the FeRu / CeO2 catalyst according to claim 1 or the FeRu / CeO2 catalyst prepared by the preparation method according to any one of claims 2 to 8, characterized in that: Used to catalyze the hydrogenolysis of plastics.

10. The use of the FeRu / CeO2 catalyst according to claim 9, characterized in that: The hydrogenolysis reaction specifically comprises the following steps: The FeRu / CeO2 catalyst and low-density polyethylene physically mixed in a mass ratio of 1:10 were added to the reactor. After the reactor was sealed, 0.1MPa N2 was filled as an internal standard and 1-3MPa H2 was filled as a reaction gas. The reaction was carried out at 200-300°C for 0.5-1h.

Citation Information

Patent Citations

  • Method for producing fuel oil and liquefied petroleum gas through catalytic conversion of waste plastics

    CN117431091A

  • Polyethylene plastic hydrogenolysis catalyst and preparation method thereof

    CN118988345A